NETRALITAS PEGAWAI NEGERI SIPIL - Aswin Eka Adhi (Badan Kepegawaian Negara | The National Civil Service Agency, 2009)
Basing on theoretical perspective, civil service neutrality which is part of bureaucratic neutrality has three theoretical basis: (1) Hegel’s neutrality, (2) ) Max’s neutrality, and (3) ) Weber’s neutrality. Hegel and Weber with their own argumentation agree that bureaucracy should be neutral, while Max argue thar bureaucracy should not be neutral. This theoretical controversion has impact on the interpretation of policy implementation in many countries, including Indonesia.